HYPERTHYROIDISM AND ATRIAL FIBRILLATION IN WOMEN OVER 40: RISK FACTORS AND MANAGEMENT STRATEGIES (JOURNAL OF ANALYTICAL SYNERGY AND SCIENTIFIC HORIZON, 2025)
Hyperthyroidism, characterized by excessive thyroid hormone production, is a well-established risk factor for atrial fibrillation (AF), particularly in women over 40. This article reviews the pathophysiological mechanisms, epidemiological data, and evidence-based management approaches for AF in hyperthyroid patients, with a focus on middle-aged and older women. We analyze key studies and clinical guidelines to provide a comprehensive overview of this critical cardiovascular-endocrine interaction.